Representation of authors and editors from countries with different human development indexes in the leading literature on tropical medicine: survey of current evidence. Issue 7450 (1st April 2004) - Keiser, Jennifer; Utzinger, Jürg; Tanner, Marcel; Singer, Burton H
Abstract: Objective To assess the current international representation of members of editorial and advisory boards and authors in the leading peer reviewed literature on tropical medicine. Design Systematic review. Main outcome measures Country affiliations, as classified by the human development index, of editorial and advisory board members of all tropical medicine journals referenced by the Institute of Scientific Information (ISI) as of late 2003 and of all contributing authors of full articles published in the six leading journals on tropical medicine in 2000-2. Results Sixteen (5.1%) of the 315 editorial and advisory board members from the 12 ISI referenced journals on tropical medicine are affiliated to countries with a low human development index and 223 (70.8%) to countries with a high index. Examination of the 2384 full articles published in 2000-2 in the six highest ranking tropical medicine journals showed that 48.1% of contributing authors are affiliated to countries with a high human development index, whereas the percentage of authors from countries with a low index was 13.7%. Articles written exclusively by authors from low ranked countries accounted for 5.0%. Our data indicate that research collaborations between a country with a high human development index and one that has either a medium or a low index are common and account for 26.5% and 16.1% of all full articles, respectively. Conclusion Current collaborations should be transformed into research partnerships, with the goals of mutual learning and institutional capacity strengthening in the developing world.